Vasopressin Receptor Antagonists in Hyponatremia: Uses and Misuses - Rondon-Berrios, Helbert; Berl, Tomas (Frontiers in Medicine, 2017)
Decreases in the concentration of sodium in plasma constitute hyponatremia, the commonest electrolyte disorder in clinical medicine. It is now well-established that its presence conveys an increased mortality risk even when the decrement is mild. In addition, recent evidence suggests that chronic and apparently asymptomatic hyponatremia is associated with increased morbidity including neurocognitive deficits and bone fractures. Furthermore, hyponatremia is associated with higher healthcare related expenses. Consequently, exploring new therapeutic strategies that increase plasma sodium in a safe and effective manner is of paramount importance. In this regard, there is scant data to support the use of traditional management strategies for hyponatremia (fluid restriction, salt tablets, loop diuretics, normal saline). Furthermore data from a large hyponatremia registry reveals the limited efficacy of these therapies. More recently vasopressin receptor antagonists provide a promising treatment for hyponatremia by targeting its most common mechanism namely increased vasopressin activity. However, uncertainty still lingers as to the optimal indications for the use of vasopressin receptor antagonists in hyponatremia and a few reports have described complications resulting from their misuse. This review summarizes the appropriate and inappropriate uses of vasopressin receptor antagonists in the treatment of hyponatremia.